Skepticism and belief in early modern England - Caldwell, Melissa M., author.
1 online resource (pages cm)
Keywords: The central thesis of this book is that skepticism was instrumental to the defense of orthodox religion and the development of the identity of the Church of England. Examining the presence of skepticism in non-fiction prose literature at four transitional moments in English Protestant history during which orthodoxy was challenged and revised, Melissa Caldwell argues that a skeptical mode of thinking is embedded in the literary and rhetorical choices made by English writers who straddle the project of reform and the maintenance of orthodoxy after the Reformation in England. Far from being a radical belief simply indicative of an emerging secularism, she demonstrates the varied and complex appropriations of skeptical thought in early modern England. By examining a selection of various kinds of literature-including religious polemic, dialogue, pamphlets, sermons, and treatises-produced at key moments in early modern England's religious history, Caldwell shows how the writers under consideration capitalized on the unscripted moral space that emerged in the wake of the Reformation. The result was a new kind of discourse--and a new form of orthodoxy--that sought both to exploit and to contain the skepticism unearthed by the Reformation.